Optimizing Hospitality Choices: A Forward Chaining and Certainty Factor-Based Expert System for Recommending 4-Star Hotels in Batam City - Caniago, Deosa Putra; Simatupang, Devid Trinaldo; Kurnia, Okki; Septiana, Reski; Sekar, M. Y. Meinadia (The Indonesian Journal of Computer Science, 2024)
Tourism and travel is the largest industry in the world with hotels as a key factor in enjoying a holiday. As the cornerstone of tourism, the hotel industry continues to develop to meet increasingly high customer expectations. The application of high technology is the key to competition between hotels, with several hotels moving towards an innovative and efficient "smart hotel" concept. This research explores the hotel industry in Batam as a unique tourism destination and industrial center. The main focus includes analyzing the level of technology adoption in Batam hotels, identifying trends and factors driving the “smart hotel” concept, and developing expert system models to improve the tourist experience. By combining the two methods of Forward Chaining and Certainty Factors in an Expert System, it is hoped that the results of this research can provide important insights regarding the development of the hotel industry in Batam and the positive impact of technology in improving the quality of service to travelers.